Produksi Kopi Robusta Sebagai Potensi Wisata Di Desa Bangelan, Kecamatan Wonosari, Kabupaten Malang (Fakultas Teknik, Universitas Brawijaya, 2024)
Bangelan Village, Wonosari District is one of the famous villages as a producer of Robusta coffee in Malang Regency. Bangelan Village has a coffee plantation of 436.02 Ha. The coffee plantation of Bangelan Village is a relic of the Dutch colonial period which is now taken over by the Company PT. Nusantara Plantation (PTPN) XII. PTPN XII coffee plantations have an important role for the economic development of the Bangelan village community. The purpose of this service is to find out the production process and its role in the economic condition of the people of Bangelan Village. The methods used in this study are observation and interview methods to obtain information related to coffee plantations ranging from production to their role in the economic condition of the community. This research is expected to provide insight for the Indonesian people regarding the role of the coffee industry in Bangelan Village.